Design, functional evaluation and biomedical applications of carbohydrate dendrimers (glycodendrimers) - Bezouska, Karel (Journal of biotechnology, 2002)
Receptors for carbohydrates of the lectin type are multisubunit and multivalent proteins with many important biological functions. In order to put their unique biological activities into use in biotechnology and biomedicine, efficient carbohydrate ligands of the glycodendrimer type have been constructed. Although these compounds may be branched into the multiple generations, structures bearing four to 16 terminal carbohydrate substituents have proved to be efficient ligands in most lectin systems. These compounds are rapidly finding important practical applications as antitumor and antiinfective compounds.
Keywords: Rats; Models, Molecular; ligandy; Carbohydrate Metabolism; biotechnologie; antivirové látky; Antineoplastic Agents; krysa rodu Rattus; Biotechnology; metabolismus sacharidů; sacharidy; Polymers; Ligands; molekulární modely; protinádorové látky; zvířata; lektiny; racionální návrh léčiv; Lectins; Drug Design; Antiviral Agents; polymery; Carbohydrates; Animals